Consumer racism: a scale modification - Abdul Latif, Samshul Amry; Abdul Talib, Asmat Nizam (Emerald Publishing, 2017)
Purpose – Consumer racism describes the act of purchase discrimination based on ethnic and/or cultural differences. As the original consumer racism scale was developed based on a Western context and environment, most of its items may be unsuitable for use in certain non-Western countries. This paper aims to modify the existing consumer racism scale to include the elements of inter-ethnic relationships, historical occurrences and political situations, which are crucial in shaping and influencing racism in a multi-religion and multi-racial context.